Assessing urban system vulnerabilities to flooding to improve resilience and adaptation in spatial planning. - Pasi, Riccardo; Viavattene, Christophe; La Loggia, Goffredo; Musco, Francesco (Springer, 2018)
Fluvial, pluvial and coastal flooding are the most frequent and costly natural hazard. Cities are social hubs and life in cities is reliant on a number of services and functions such as housing, healthcare, education and other key daily facilities. Urban flooding can cause significant disruption to these services and wider impacts on the population. These impacts may be short or long with a variably spatial scale: Urban systems are spatially distributed and the nature of this can have significant effects on flood impacts. From an urban-planning perspective, measuring this disruption and its consequences is fundamental in order to develop more resilient cities. Whereas the assessment of physical vulnerabilities and direct damages is commonly addressed, new methodologies for assessing the systemic vulnerability and indirect damages at the urban scale are required. The proposed systemic approach recognizes the city as a collection of sub-systems or functional units (such as neighborhoods and suburbs), interconnected through the road network, providing key daily services to inhabitants (e.g., healthcare facilities, schools, food shops, leisure and cultural services). Each city is part of broader systems - which may or may not match administrative boundaries - and, as such, needs to be connected to its wider surroundings in a multi-scalar perspective. The systemic analysis, herein limited to residential households, is based on network-accessibility measures and evaluates the presence, the distribution among urban units and the redundancy of key daily services. Trying to spatially sketch the existence of systemic interdependences between neighborhoods, suburbs and municipalities, the proposed method highlights how urban systemic vulnerability spreads beyond the flooded areas. The aim is to understand which planning patterns and existing mixed-use developments are more flood resilient, thereby informing future urban development and regeneration projects. The methodology has been developed based on GIS and applied to an Italian municipality (Noale) in the metropolitan area of Venice, north-eastern Italy.
Keywords: Raumplanung; Stadtplanung; Überschwemmung; Hochwasser; Starkregen; Resilienz; GIS